Effects of alcohol warning labels on alcohol-related cognitions among German adolescents: A factorial experiment. (June 2021) - Morgenstern, Matthis; Dumbili, Emeka W.; Hansen, Julia; Hanewinkel, Reiner
Highlights: Many countries have mandated alcohol warning labels (AWL) on alcoholic beverages. AWL exposure can increase knowledge of children and adolescents. Older children and adolescents show a stronger reaction towards AWL. Pictorial AWL elicit stronger reactions than text-only AWL. Abstract: There is evidence that alcohol warning labels (AWL) can have preventive effects on alcohol-related cognitions and behavior, but it is less clear how children and adolescents react to AWL. A total of 9260 German students aged 10–17 participated in a three-factorial experiment, embedded in a health survey. The first experimental factor was the position of the AWL on the questionnaire (before vs. after alcohol items). The second factor was the type of AWL (text only vs. text plus picture). The third factor was the content of the AWL (one out of a pool of ten). Dependent variables were knowledge about alcohol-related risks, self-reports of alcohol use, and negative emotions. Regression analyses revealed that exposure to an AWL significantly increased knowledge about alcohol-related risks. AWL exposure did not influence self-reports of alcohol use in the total sample, but a significant interaction for PositionXAge indicated that older students (15+ years) less frequently reported lifetime (79.8% vs. 84.2%) and current (50.5% vs. 56.6%) use of alcohol if they were exposed to an AWL. Overall, text-only AWL elicited less negative emotions than text-and-picture based AWL. The experiment indicates that exposure to an AWL affected alcohol-related cognitions of children and adolescents. This was true for both, text-based or picture-and-text-based labels. Pictorial messages seem to be more potent to elicit emotions, at least for recipients that already have experience with alcohol use. Future research needs to further explore the long-term effects of repeated exposure to the same message contents.